Application of Traditional Chinese Medicine ointment rubbing technique in a patient undergoing hip replacement for necrosis of the femoral head (中药膏摩技术在1例股骨头坏死行髋关节置换术患者中的应用) - YANG Ruxin (杨如心); WU Benmeng (吴本蒙); KONG Hua (孔华); XING Liang (邢亮) (中西医结合护理)
Necrosis of the femoral head is a common refractory disease. At present, conventional open surgery is still used in most clinics, and postoperative pain, swelling and ecchymosis are common postoperative complications. This paper reviewed the clinical data of a patient undergoing hip replacement for femoral head necrosis. Based on the comprehensive nursing assessment, the Traditional Chinese Medicine ointment rubbing technique was carried out to relieve the postoperative pain, swelling and local ecchymosis, and improve the patient's comfort and early postoperative recovery. (股骨头坏死是一种常见的难治性疾病, 目前临床多采用传统的开放手术, 术后疼痛、肿胀及瘀斑是术后常见并发症。本文回顾1例股骨头坏死行髋关节置换术患者临床资料, 在加强护理评估的基础上, 运用中药膏摩技术缓解术后疼痛、肿胀及局部瘀斑, 旨在提高患者舒适度, 促进术后早日康复。)